2000
DOI: 10.1046/j.1464-5491.2000.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced albuminuric response to atrial natriuretic peptide in normoalbuminuric patients with Type 1 diabetes mellitus – a pilot study

Abstract: ANP increases urine albumin excretion rate in normoalbuminuric Type 1 DM patients, and this effect is more pronounced than in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In humans, the albuminuric action of ANP was first reported in healthy individuals, who were infused with extremely high doses of the hormone [26], though subsequent studies in young controls failed to demonstrate a significant albuminuric response to intravenous infusions of low dose ANP [10,12]. Our data demonstrates a non-significant trend towards an albuminuric response to low dose ANP in an older control group.…”
Section: Discussionsupporting
confidence: 40%
See 4 more Smart Citations
“…In humans, the albuminuric action of ANP was first reported in healthy individuals, who were infused with extremely high doses of the hormone [26], though subsequent studies in young controls failed to demonstrate a significant albuminuric response to intravenous infusions of low dose ANP [10,12]. Our data demonstrates a non-significant trend towards an albuminuric response to low dose ANP in an older control group.…”
Section: Discussionsupporting
confidence: 40%
“…The rises in urinary cGMP and urine sodium excretion were similar and there was an almost identical diuresis between the diabetic and control groups. Previous studies have shown either blunted or normal diuretic and natriuretic responses to ANP in type-1 diabetic patients [10,12,20]. We were careful to exclude patients with microalbuminuria, so our data clearly shows normal renal sensitivity to the natriuretic effects of ANP in type-2 diabetes in the absence of microalbuminuria.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations